EVALUASI PERHITUNGAN HARGA POKOK PRODUKSI BOLA PLASTIK PADA CV EKA JAYA SAKTI PLASINDO DI KABUPATEN BOYOLALI - Yuwono Andi Saputro (Universitas Slamet Riyadi, 2015)
The purpose of this study was to Evaluate the calculation of cost of production in the CV Eka Jaya Sakti Plasindo and evaluate the profit-loss calculation in the CV Eka Jaya Sakti Plasindo this study using case studies conducted on the owners and employees of the company plastic ball CV Eka Jaya Sakti Plasindo Boyolali district. The data needed is a general description of firms plastic ball CV Eka Jaya Sakti Plasindo respondents about the recording of transactions, cost accounting, and human resources. The technique of collecting data by interview and observation. The primary data of enterprise transaction data and a number of statements submitted to the owner of the company. Results of the analysis showed that the preparation of the financial statements contained in the company is not in accordance with the theories that have been used in general, so the format to be proposed by using Variable Costing is expected to be used to be able to meet the needs of enterprise reporting for calculation of profit and loss determining profit actually. Keywords: Manufacturing, Income, Variable Costing, Cost of Production.